Analisis Ketimpangan Regional Dan Identifikasi Sektor Basis Antar Kecamatan Di Kabupaten Blora Tahun 2011-2015 - Hayati, Suci Nur; , Dr. Didit Purnomo, M.Si (2017)
basis in Blora 2011-2015. This study uses secondary data, Gross Domestic Product (GDP) by Industrial Basic Konstran Price Base Year 2010, the GDP per capita, number of population and economic growth. The analysis method used in this research include analysis Willionson Index, Entropy index theil, Location Quantient (LQ), growth, and Klassen Typology analysis. Based on the analysis showed that the level of inequality between districts in Blora very high. On the index Williomson indicates the degree of inequality in Blora in the year 2011 to 2015 amounted to 0.852 while in index Entropy Theil tend to fluctuate with an average of 16.916, the analysis Location Quantient (LQ) bases sector that dominates in Blora is a sector of agriculture, forestry and Fisheries. Based Klassen Typology analysis that divides the area into three classification areas. 12 of the 16 districts in Blora classified area is relatively underdeveloped concluded that pertained Blora Regency that are lagging behind. From the analysis, suggested to the government of Blora to address regional imbalances between districts in order to avoid imbalances that lead to social inequalities and the government needs to increase the basic sector to advance the region's economy in order to reduce regional imbalances.